How the COVID-19 Pandemic Is Reshaping the Trade Landscape and What to Do About It - Sébastien Jean (Intereconomics, 2020)
The COVID-19 pandemic carries heavy threats, and preserving stable and coordinated international trade relations will be essential to avoid catastrophic disorders or conflicts.
Keywords: 330